ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP PEMBERITAAN DUGAAN SERANGAN SIBER BANK SYARIAH INDONESIA DI MEDIA BBC - Musdalifah Musdalifah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
This study aims to analyze the news of the alleged cyber attack of Bank Syariah Indonesia in the BBC media using Norman Fairclough's Critical Discourse Analysis. The problems focused on 1) framing BBC news, 2) framing the ideology of BBC news, 3) religious dimension in framing news. The type of research used is qualitative with secondary data sources, namely news texts posted by the BBC entitled